Bioelectrochemical methane (CH4) production in anaerobic digestion at different supplemental voltages. (December 2017) - Choi, Kwang-Soon; Kondaveeti, Sanath; Min, Booki
Highlights: The difference in applied voltage have significantly altered the MEC performance. Amplification in hydrolysis process was noted in MEC with comparison to conventional AD process. At 1.0 V, maximum activity of electroactive methanogenic bacteria is achieved interm of methane yield and COD removal. Acetate and Propionate were noticed as a major intermediator compounds during CH4 generation. Abstract: Microbial electrolysis cells (MECs) at various cell voltages (0.5, 0.7 1.0 and 1.5 V) were operated in anaerobic fermentation. During the start-up period, the cathode potential decreased from −0.63 to −1.01 V, and CH4 generation increased from 168 to 199 ml. At an applied voltage of 1.0 V, the highest methane yields of 408.3 ml CH4 /g COD glucose was obtained, which was 30.3% higher than in the control tests (313.4 ml CH4 /g COD glucose). The average current of 5.1 mA was generated at 1.0 V at which the maximum methane yield was obtained. The other average currents were 1.42, 3.02, 0.53 mA at 0.5, 0.7, and 1.5 V, respectively. Cyclic voltammetry and EIS analysis revealed that enhanced reduction currents were present at all cell voltages with biocatalyzed cathode electrodes (no reduction without biofilm), and the highest value was obtained with 1 V external voltage.